Summer Dust Emissions From the Etosha Pan, Namibia: The Role of the Namib Anabatic‐Sea Breeze System. Issue 6 (10th March 2023) - Clements, Matthew; Washington, Richard
Abstract: This paper utilizes Aerosol Index (AI) data from the Total Ozone Mapping Spectrometer (TOMS) instrument, along with ERA5 reanalysis data, to identify atmospheric processes contributing to the uplift of dust from the Etosha Pan through the annual cycle. Etosha is one of the most prominent source areas in the Southern Hemisphere, although very little is known about its meteorology outside of the peak dust season (August–October). Emissions in December (AI = 1.6) are shown to be comparable to those in September (AI = 1.7), the dustiest month in the TOMS record. Unlike in September however, when a nocturnal low‐level jet is the primary emission mechanism, uplift in December is associated with an anabatic‐sea breeze that develops along the Namib coast, and propagates inland to reach Etosha during the evening. The system is a response to the thermal contrast between the elevated interior plateau and the adjacent waters of the cool Benguela Upwelling System, and so is at its strongest during austral summer, when the area of maximum diabatic heating shifts south over southern Africa. Topographic channeling of the flow through the east‐west orientated Hoanib River valley is shown to facilitate the inland propagation of the anabatic‐sea breeze, and explains the persistence of the system at Etosha's latitude. Evening surface winds at Etosha, associated with the anabatic‐sea breeze, are significantly stronger in the dustier December months, when diabatic heating over the subcontinent and hence the zonal thermal gradient are enhanced. Plain Language Summary: This paper uses satellite and meteorological data to identify the features of southern Africa's weather and climate that contribute to dust emission from the Etosha Pan throughout the year. Etosha is an important source of dust in the Southern Hemisphere, however very little work has been conducted there outside of the winter season, when emissions are at their highest. From the satellite data, it is shown that December is just as dusty as some of the winter months, however there is a difference in the low‐level winds between the two seasons; in winter, emissions are driven by a morning peak in surface wind speeds, whereas emissions in December are driven by maximum surface winds during the evening. This evening peak in surface winds is shown to coincide with the arrival of a sea breeze at Etosha, with the system a response to the strong heating of the southern African plateau at this time of year. Evening surface winds associated with the sea breeze are stronger during the dustiest December months at Etosha, and are driven by enhanced heating over the subcontinent. Key Points: An anabatic‐sea breeze helps to drive austral summer dust emissions from one of the Southern Hemisphere's most prominent source areas The anabatic‐sea breeze is present throughout the year, however is at its strongest, and propagates furthest inland during austral summer Variability in the strength of the system is driven by changes in the pattern of diabatic heating over the interior of southern Africa